Employee’s attitude and managerial support on lean benefits - Vatumalai, Sivaprakash (2015)
This research aims to determine the factors that influence lean manufacturing performance in Malaysian automotive industry. The objectives of this study are to identify the employee’s perception towards the level of lean manufacturing performance, to identify the relationship between senior manager’s support and lean manufacturing performance, to analyze the relationship between employee’s attitude and lean manufacturing performance and to determine the most influential senior manager’s support and employee’s attitude factor that affect lean manufacturing performance in Malaysian automotive industry based on the shop floor employee’s perception. Questionnaires were used as an instrument to collect data from 110 shop floor employees which consist of technicians and supervisors from 13 Malaysian automotive component manufacturing companies. The data was analyzed by using Statistical Package for Social Sciences (SPSS) version 16.0 in the form of frequency, percentage, mean and multiple regression models. The findings show that the shop floor employees perceived positively the lean manufacturing performance in Malaysian automotive industry. Based on the shop floor employee’s perception, there is a significant relationship between senior manager’s support and employee’s attitude towards the lean manufacturing performance in Malaysian automotive industry. Moreover, the most influential senior manager’s support factor which affects lean manufacturing performance in Malaysian automotive industry is having a clear vision. In addition, the most influential employee’s attitude factor which affects lean manufacturing performance in Malaysian automotive industry is openness towards change. Based on the overall result, shop floor employees believe that senior manager’s support is the most influential factor that affects lean manufacturing performance in Malaysian automotive industry.